Xanthine oxidase activity regulates human embryonic brain cells growth - Danielyan, K.E.; Kevorkian, G.A. (Вiopolymers and Cell, 2011)
Aim. Involvement of Xanthine Oxidase (XO; EC1.1.3.22) in cellular proliferation and differentiation has been
suggested by the numerous investigations. We have proposed that XO might have undoubtedly important role
during the development, maturation as well as the death of human embryos brain cells. Methods. Human abortion material was utilized for the cultivation of brain cells (E90). XO activity was measured by the formation of
uric acid in tissue. Cell death was detected by the utility of Trypan Blue dye. Results. Allopurinol suppressed the
XO activity in the brain tissue (0.12 ± 0.02; 0.20 ± 0.03 resp., p ≤ 0.05). On day 12th the number of cells in the
culture treated with the Allopurinol at the early stage of development was higher in comparison with the Control
(2350.1 ± 199.0 vs 2123 ± 96) and higher in comparison with the late period of treatment (1479.6 ± 103.8, p <
< 0.05). In all groups, the number of the dead cells was less than in Control, indicating the protective nature of
Allopurinol as an inhibitor of XO. Conclusions. Allopurinol initiates cells proliferation in case of the early
treatment of the human brain derived cell culture whereas at the late stages it has an opposite effect.
Keywords: xanthine oxidase, human embryonic brain cells, proliferation, cell death. Мета. Важливість функціонування ксантиноксидази (КО) в процесах проліферацї і диференціації клітин доведено багатьма вченими. Ми припустили, що КО виконує незамінну роль у процесах
розвитку, дозрівання, а також загибелі клітин мозку ембріона
людини. Методи. Абортивний матеріал людини застосовано для
культивування клітин (E90). Активність КО визначали за кількістю сечової кислоти в тканині; клітинну смерть – з використанням трипанового синього. Результати. Алопуринол, згідно із нашим дослідженням, пригнічує активність КО (0,12 ± 0,02; 0,20 ±
± 0,03 відповідно, p ≤ 0,05). На 12-й день кількість клітин у культурі, у яку вносили алопуринол, починаючи з перших етапів розвитку, була вищою, ніж у контролі (2350,1 ± 199,0 vs 2123 ± 96),
та перевищувала кількість клітин у культурі, до якої додавали
алопуринол на більш пізніх стадіях росту і розвитку (1479,6 ±
± 103,8, p < 0,05). В усіх культурах кількість мертвих клітин виявилася нижчою порівняно з контролем, що вказує на захисні
властивості алопуринолу як інгібітора КО. Висновки. Алопуринол
ініціює клітинну проліферацію на ранніх етапах розвитку клітинної культури та пригнічує клітинний ріст на пізніших стадіях.
Ключові слова: ксантиноксидаза, ембріональні клітини мозку
людини, проліферація, клітинна смерть. Цель. Важность функционирования ксантиноксидазы (КО) в
процессах пролиферации и дифференциации клеток доказана рядом ученых. Мы предположили, что КО выполняет незаменимую
роль в процессах развития, созревания, а также смерти клеток
мозга эмбриона человек. Методы. Человеческий абортивный материал применен для культивирования клеток (E90). Активность
КО определяли по количеству мочевой кислоты в ткани; клеточную смерть – с использованием трипанового синего. Результаты. Аллопуринол, согласно нашим исследованиям, подавляет активность КО (0,12 ± 0,02; 0,20 ± 0,03 соответственно, p ≤ 0,05).
На 12-й день количество клеток в культуре, в которую вносили
аллопуринол, начиная с первых этапов развития, было выше, чем в
контроле (2350,1 ± 199,0 vs 2123 ± 96), и превышало количество
клеток в культуре, в которую добавляли аллопуринол на более поздних стадиях роста и развития (1479,6 ± 103,8, p < 0,05). Во всех
культурах количество мертвых клеток оказалось ниже, чем в
контроле, что указывает на защитные свойства аллопуринола
как ингибитора КО. Выводы. Аллопуринол инициирует клеточную пролиферацию на ранних этапах развития клеточной культуры и подавляет клеточный рост на более поздних стадиях.
Ключевые слова: ксантиноксидаза, эмбриональные клетки
мозга человека, пролиферация, клеточная смерть.